2022
DOI: 10.3390/cancers14020334
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA and 68Ga-DOTA-RM2 PET/MRI in Recurrent Prostate Cancer: Diagnostic Performance and Association with Clinical and Histopathological Data

Abstract: The aim of the present study is to investigate and compare the performances of 68Ga-PSMA and 68Ga-DOTA-RM2 PET/MRI in identifying recurrent prostate cancer (PCa) after primary treatment and to explore the association of dual-tracer PET findings with clinical and histopathological characteristics. Thirty-five patients with biochemical relapse (BCR) of PCa underwent 68Ga PSMA PET/MRI for restaging purpose, with 31/35 also undergoing 68Ga-DOTA-RM2 PET/MRI scan within 16 days (mean: 3 days, range: 2–16 days). Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Although the detection rate of 95% for the primary tumor is similar that in to our study, the positivity rates for lymph nodes were lower (37% for 68 Ga-PSMA11, 21% for 68 Ga-RM2). Apart from a negative 68 Ga-RM2 finding in 1 participant, concordant uptake was seen between 68 Ga-RM2 and 68 Ga-PSMA11 (38). The incongruent uptake pattern in our cohort might be due to our more heterogeneous groups of intermediate-and high-risk PC.…”
Section: Discussionmentioning
confidence: 46%
“…Although the detection rate of 95% for the primary tumor is similar that in to our study, the positivity rates for lymph nodes were lower (37% for 68 Ga-PSMA11, 21% for 68 Ga-RM2). Apart from a negative 68 Ga-RM2 finding in 1 participant, concordant uptake was seen between 68 Ga-RM2 and 68 Ga-PSMA11 (38). The incongruent uptake pattern in our cohort might be due to our more heterogeneous groups of intermediate-and high-risk PC.…”
Section: Discussionmentioning
confidence: 46%
“…There were still 55 studies for full-text screening, and another 18 were disqualified due to the following reasons: non-English studies (n = 3); cannot extract positivity rate data (n = 7); and different radiotracers (n = 8). 37 studies that satisfied the criteria for the meta-analysis were finally included, including 25 articles for 68 Ga-PSMA-11 PET/CT (14-38) and 13 articles for 68 Ga-PSMA-11 PET/MRI (4,26,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). One of the studies included not only 68 Ga-PSMA-11 PET/CT but also 68 Ga-PSMA-11 PET/MRI.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…A small peptide called RM2, with the chelator DOTA coupled to D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2 via the cationic spacer 4-amino-1-carboxymethyl-piperidine (referred to as DOTA-RM2 in this study), has shown to be one of the potent antagonists with excellent pharmacokinetic properties, indicating that gallium-68 labeled DOTA-RM2 may serve as a good candidate for positron emission tomography (PET) imaging [ 15 ]. Currently, GRPr imaging appears to be complementary to prostate-specific membrane antigen (PSMA) imaging in preclinical studies and preliminary human studies in patients with primary limited prostate cancer [ 16 , 17 ]. Several studies have shown that in recurrent prostate cancer, RM2-PET imaging may be more beneficial in patients with negative findings on conventional imaging, compared to PSMA-PET [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%